Healthy Food Serving Strategies to Increase Toddlers' Appetite - Khayati, Ni’matul (Annual Conference on Islamic Early Childhood Education (ACIECE), 2024)
Appetite variability in toddlers poses a significant challenge for parents, often impacting their nutritional intake and overall development. Good eating habits are crucial for ensuring optimal growth and health in young children, yet low appetite can lead to malnutrition and developmental setbacks. This study explores effective food presentation strategies to improve appetite among toddlers. Conducted as a field study with a qualitative approach, this research observed 13 purposively selected toddlers aged 1-5 years. Data were collected through direct observation and interviews with parents to identify strategies that stimulate appetite and enhance nutritional intake. Results reveal that creative and varied food presentations successfully enhance toddler appetite. For instance, using visually appealing shapes, colors, and textures significantly increased interest in consuming healthy foods. These findings underscore the importance of parental involvement in creating meal plans that are both nutritious and engaging, allowing toddlers to enjoy a balanced diet consistently. The study suggests that by adopting these creative presentation techniques, parents and caregivers can support better nutrition and growth in children. Further research could explore the long-term impacts of consistent meal presentation strategies on overall dietary habits and health outcomes.